2008
DOI: 10.1007/s00330-008-1016-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of detecting breast cancer on computed radiographic (CR) mammograms: comparison of hard copy film, 3-megapixel liquid-crystal-display (LCD) monitor and 5-megapixel LCD monitor

Abstract: The purpose was to compare observer performance in the detection of breast cancer using hard-copy film, and 3-megapixel (3-MP) and 5-megapixel (5-MP) liquid crystal display (LCD) monitors in a simulated screening setting. We amassed 100 sample sets, including 32 patients with surgically proven breast cancer (masses present, N = 12; microcalcifications, N = 10; other types, N = 10) and 68 normal controls. All the mammograms were obtained using computed radiography (CR; sampling pitch of 50 mum). Twelve mammogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…However, soft-copy reading has the advantage of optimizing the display for each mammogram. A recent study by receiver operating characteristics (ROC) analysis demonstrated there were no significant differences between hard-copy and soft-copy reading [14][15][16]. The soft-copy reading in these studies was performed by using monochrome crystal ray tube (CRT) or liquid-crystal display (LCD) monitors with old specifications, for example 8-bit gray scale.…”
Section: Interpretation Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, soft-copy reading has the advantage of optimizing the display for each mammogram. A recent study by receiver operating characteristics (ROC) analysis demonstrated there were no significant differences between hard-copy and soft-copy reading [14][15][16]. The soft-copy reading in these studies was performed by using monochrome crystal ray tube (CRT) or liquid-crystal display (LCD) monitors with old specifications, for example 8-bit gray scale.…”
Section: Interpretation Methodsmentioning
confidence: 97%
“…Then even a 5-MP monitor has a critical shortage of pixels and requires 2-fold magnification of the images with sampling pitch at 50 lm to display the images at the same number of pixels (Tables 3, 5). The past report demonstrated that diagnostic performance of digital mammograms with 3-MP LCD monitors and 5-MP LCD or CRT monitors was equivalent to each other [15,18]. This is probably because both of them allowed magnified observation.…”
Section: Monitors In Soft-copy Readingmentioning
confidence: 93%
“…Recently, Yamada et al also reported that soft-copy reading using 3 and 5 MP displays is comparable to hard-copy reading for detecting breast cancer using a sampling pitch with a 50-lm imaging plate [7].…”
Section: Monitor Issuesmentioning
confidence: 96%
“…High-grade (so-called medical purpose) LCDs, such as the 5-megapixel (MP) LCD, are recommended for soft-copy reading in digital mammography [10][11][12].…”
Section: Introductionmentioning
confidence: 99%